Upaya Peningkatan Kompetensi Profesional Guru Di Era Revolusi Industri 4.0 - Berliana Berliana; Dian Andarini (PT. ALHAFI BERKAH INDONESIA, 2023)
A teacher is an educational staff who holds a huge responsibility in educating the nation's children. Nowadays we have entered the era of industrial revolution 4.0. Where technology is no longer foreign to us and is often used in everyday life. Likewise in terms of education. Teachers as educators are required to continue learning in order to improve their professional competence, so that a teacher is obliged to improve their knowledge, knowledge and expertise in accordance with current technological developments and times. However, as the facts show, there are still many teachers who have not been able to follow the industrial revolution 4.0 era because teachers are still overwhelmed and do not understand the use of technology in this era. Therefore, as a teacher you must strive to improve your professional competence and be able to adapt to the era of industrial revolution 4.0.